1997
DOI: 10.1128/aac.41.7.1531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2',3'-dideoxyinosine on Toxoplasma gondii cysts in mice

Abstract: The activity against Toxoplasma gondii of 2',3' dideoxyinosine (ddI), an anti-human immunodeficiency virus drug, was examined in an in vitro and in vivo study. Cell cultures infected with a strain known to cause chronic infections were used to show the dose-dependent effect of this drug compared with spiramycin and sulfadiazine. When a dose of 4 microg/ml was used, no infected THP-1 cells or parasites were found after 60 h of incubation. An electron-microscopic study confirmed that after 12 h at 1 microg/ml, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…(2)), were found to exhibit potent antimalarial activity towards the erythrocytic stage of P. knowlesi, the agent of simian malaria [63]. Moreover, unpublished results from our laboratory suggest that the effect of DDI on Plasmodium is similar to its reported activity against the other apicomplexan protozoans Cryptosporidum parvum and Toxoplasma gondii [64,65].…”
Section: Exploitation Of Pfent1 As a Route For Selective Drug Uptakesupporting
confidence: 63%
“…(2)), were found to exhibit potent antimalarial activity towards the erythrocytic stage of P. knowlesi, the agent of simian malaria [63]. Moreover, unpublished results from our laboratory suggest that the effect of DDI on Plasmodium is similar to its reported activity against the other apicomplexan protozoans Cryptosporidum parvum and Toxoplasma gondii [64,65].…”
Section: Exploitation Of Pfent1 As a Route For Selective Drug Uptakesupporting
confidence: 63%
“…We have successfully developed an in vitro culture model using the non-adherent myelomonocytic human cell line THP-1 which provides an enhanced versatility and allows the determination of the various parasitic stages [3]. We used this system to test 2P,3P-dideoxyinosine (ddI), a purine analog active against HIV and Toxoplasma gondii in vitro and in vivo [4,5]. Paromomycin, an aminoglycoside reported to exert some activity against C. parvum in vitro [6^8], in animal models [9^11] and AIDS patients [12] was used as a positive control.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the purine analog 2′,3′‐dideoxyinosine (ddI) was highly active against T. gondii cultured in THP‐1 cells and suggested the purine salvage pathway of this parasite as a promising chemotherapeutic target [4,5]. As an Apicomplexan, C. parvum possesses some different metabolic pathways [13] and also lacks a de novo purine synthesis, as reported recently [14].…”
Section: Resultsmentioning
confidence: 77%
“…This molecule is taken up by the monocyte/macrophage populations, especially the resting cells [18,19] where its metabolite ddATP is found, as well as ddI‐derived radioactivity incorporated into the cell DNA and RNA pool [20]. In contrast to T. gondii where low concentrations were rapidly active [4,5], the lower inhibition of C. parvum probably reflects the different metabolic activity of this parasite. Furthermore, ddI must penetrate into the THP‐1 cells where it may be metabolized before entering the parasite, thus reducing its subsequent inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%